Generation of BAF53b‐Cre transgenic mice with pan‐neuronal Cre activities. Issue 7 (23rd June 2015) - Zhan, Xiaoming; Cao, Mou; Yoo, Andrew S.; Zhang, Zilai; Chen, Lei; Crabtree, Gerald R.; Wu, Jiang I.
Summary Molecular and functional studies of genes in neurons in mouse models require neuron‐specific Cre lines. The current available neuronal Cre transgenic or knock‐in lines either result in expression in a subset of neurons or expression in both neuronal and non‐neuronal tissues. Previously we identified BAF53b as a neuron‐specific subunit of the chromatin remodeling BAF complexes. Using a bacteria artificial chromosome (BAC) construct containing the BAF53b gene, we generated a Cre transgenic mouse under the control of BAF53b regulatory elements. Like the endogenous BAF53b gene, we showed that BAF53b‐Cre is largely neuron‐specific. In both central and peripheral nervous systems, it was expressed in all developing neurons examined and was not observed in neural progenitors or glial cells. In addition, BAF53b‐Cre functioned in primary cultures in a pan‐neuron‐specific manner. Thus, BAF53b‐Cre mice will be a useful genetic tool to manipulate gene expression in developing neurons for molecular, biochemical, and functional studies. genesis, 53:440–448, 2015. © 2015 Wiley Periodicals, Inc.